On the stability of solutions of a quasilinear uncertain system - Martynyuk-Chernienko, Yu. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We generalize the Lyapunov direct method, which can be used for establishing new conditions of the uniform asymptotic stability of solutions of an uncertain system with respect to an invariant moving set.